Vegetación arbórea y arbustiva de la cuenca del Río Tinto (Huelva, España) - Fuente García, Vicenta de la; Rufo Nieto, Lourdes (Lazaroa, 2011)
Results from the phytosociological study of the forest and pre-forest vegetation of the Tinto river basin are presented. Eleven associations that belong to Quercetea ilicis (Sanguisorbo hybridae-Quercetum suberis, Pyro bourgaeanae-Quercetum rotundifoliae, Myrto communis-Quercetum rotundifoliae, Asparago albi-Rhamnetum oleoidis, Osyrio quadripartitae- Juniperetum turbinatae, Phillyreo angustifolie-Arbutetum unedonis), Salici purpureae-Populetea nigrae (Ficario ranunculoidis-Fraxinetum angustifoliae, Scrophulario scorodoniae-Alnetum glutinosae, Oenantho crocatae-Nerietum oleandri, Nerio oleandri-Salicetum pedicellatae) and Rhamno-Prunetea (Lonicero hispanicae-Rubetum ulmifolii) have been recognized and described. Myrto communis-Quercetum rotundifoliae quercetosum broteroi is proposed as a new syntaxon. The phytosociological tables for each studied plant community are also included or mentioned.